Recommendations on the EAEU Marketing Authorisation Procedures to Optimise the Performance of Regulatory Affairs Specialists - E. M. Rychikhina; O. G. Tkachenko; V. V. Kosenko (Регуляторные исследования и экспертиза лекарственных средств, 2023)
Since 2021, the marketing authorisation (MA) of new medicinal products in the Russian Federation has been carried out according to the Rules of Marketing Authorisation and Assessment of Medicinal Products for Human Use that are implemented by Decision No. 78 of the Council of the Eurasian Economic Commission dated 3 November 2016. The Member States of the Eurasian Economic Union (EAEU) must fully transition to the new regulatory framework by 31 December 2025. Therefore, MA holders are required to bring their existing product dossiers into compliance with EAEU requirements and continue submitting new product applications and dossier variations. Under the circumstances, the burden on regulatory authorities has increased significantly, regulatory mechanisms have become more complicated, and applicants have faced the challenge of swift adaptation to the latest requirements. To contribute towards the success of regulatory submissions, this article covers the sequence of regulatory procedures, the scope of work, and recommendations on dividing the procedures into stages, optimising each stage, determining goals and priorities, and assessing timelines and possible risks. To make the approval process more efficient, the authors illustrate the application of different procedures throughout a typical lifecycle of a dossier.